2010
DOI: 10.1002/yea.1818
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide screen of Saccharomyces cerevisiae for killer toxin HM‐1 resistance

Abstract: We screened a set of Saccharomyces cerevisiae deletion mutants for resistance to killer toxin HM-1, which kills susceptible yeasts through inhibiting 1,3-beta-glucan synthase. By using HM-1 plate assay, we found that eight gene-deletion mutants had higher HM-1-resistance compared with the wild-type. Among these eight genes, five -ALG3, CAX4, MNS1, OST6 and YBL083C -were associated with N -glycan formation and maturation. The ALG3 gene has been shown before to be highly resistant to HM-1. The YBL083C gene may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The fps1 cells also showed diphospho‐Hog1 and ‐Slt2p inductions (Figure , fps1 ). It was reported that the high HM‐1‐resistance of the alg3 cell is derived from lack of HM‐1 binding to the plasma membrane receptor (Miyamoto et al ., ). Diphospho‐Hog1p and ‐Slt2p were not induced in alg3 cells (Figure A, B, alg3 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The fps1 cells also showed diphospho‐Hog1 and ‐Slt2p inductions (Figure , fps1 ). It was reported that the high HM‐1‐resistance of the alg3 cell is derived from lack of HM‐1 binding to the plasma membrane receptor (Miyamoto et al ., ). Diphospho‐Hog1p and ‐Slt2p were not induced in alg3 cells (Figure A, B, alg3 ).…”
Section: Resultsmentioning
confidence: 97%
“…These facts are contrary to the believed fungicidal mechanism of HM‐1, an inhibition of 1,3‐ β ‐glucan synthesis. In addition, it was reported that HM‐1 binds with mannoproteins of the yeast cell wall and plasma membrane (Kimura et al ., , ; Miyamoto et al ., ). Thus, we postulate that HM‐1 has a two‐step action on the cell wall‐disturbing mechanism: (a) binding and insertion to cell wall structures (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nowadays, a particular interest in yeast killer strains and corresponding secreted toxins has emerged. Both of those have found application in industry (food protection from spoiling, wine production), agriculture (phytopathogen control), or medicine (creation of new generation vaccines and antibiotics, development of antifungal immunotherapies) (Goretti et Performing the experiments with the W. saturnus, K. lactis, and P. anomala toxins, colonies from the S. cerevisiae libraries were manually arrayed on the agar plates, and the growth of mutants was further tested either in solid or liquid media (Conti et al, 2008;Huang et al, 2008;Miyamoto et al, 2011). In the case of K1 and K28 toxins, a different approach was used.…”
Section: Introductionmentioning
confidence: 99%